Media Sosial dan Edukasi Sejarah Dakwah Islam: Analisis Kreativitas Pengembangan Konten Instagram @gen.saladin - Nuraini, Fira Pujia; Deddy Mulyana; Maimon Herawati; Efi Fadilah (Jurnal Komunikasi Islam, 2024)
The presence of social media, especially Instagram, is a blessing for Muslim content creators in teaching Islamic da’wah history. The textual, visual, and auditory features in Instagram allow them to create educational content that can bridge Islamic history information and modern understanding, making it easier to understand and not boring. This study examines an Instagram account @gen.saladin in creating creative means of Islamic history education. Using qualitative content analysis and a media ecology approach, the results of the study have revealed that to create creative educational content about Islamic history, @gen.saladin emphasizes the use of contemporary terms, mentioning film titles, song lyrics, or current news when discussing topics of Islamic da’wah history. Hence, it appears more relevant and interesting to the audience.